Sulfur-containing oligomer, application thereof and optical material composition

By using sulfur-containing oligomers of specific structures, high refractive index optical materials are obtained through click chemical reactions, and the problem of insufficient refractive index of existing optical materials is solved, and a balance between high refractive index and excellent optical properties is achieved.

CN119708487AInactive Publication Date: 2025-03-28WUHAN SUNSHINE OPTOELECTRONICS TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411936728.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The refractive index of existing organic optical materials is insufficient and cannot meet the optical performance requirements of advanced optical devices. At the same time, high refractive index will lead to increased dispersion and reduced imaging quality.

Method used

By using a sulfur-containing oligomer with a specific structure, a high refractive index oligomer is obtained by reacting a dithiol compound or a monomer containing an unsaturated group at the end, and a click chemical reaction between a thiol group and a double bond.

Benefits of technology

It has achieved a high refractive index optical material, with adjustable refractive index in the range of 1.65-1.75, high transmittance, and excellent optical properties such as ABE number and extinction coefficient.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005211681460000042
    Figure BDA0005211681460000042
  • Figure BDA0005211681460000044
    Figure BDA0005211681460000044
  • Figure BDA0005211681460000051
    Figure BDA0005211681460000051
Patent Text Reader

Abstract

The invention belongs to the technical field of optical materials, and particularly relates to a sulfur-containing oligomer, application thereof and an optical material composition. According to the invention, the dimercapto compound or the dimercapto compound reacts with the monomer containing the unsaturated group at the tail end, the high-refraction oligomer is obtained by adopting the click chemical reaction between the mercapto group and the double bond, the S element is retained on the main chain after the reaction is finished, and the content of the S element in the finally obtained oligomer is very high, so that the refractive index is greatly improved. Moreover, the monomer containing the unsaturated group contains an alkyl chain, so that the flexibility of the oligomer is improved, and the obtained optical resin has good flowability and mechanical property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of optical materials, and in particular relates to a sulfur-containing oligomer and application thereof and an optical material composition. Background Art

[0002] At present, high-performance optical materials are the cornerstone for achieving high performance, integration and lightweight of advanced optical devices. They have extensive and important applications in the fields of electronic communications, automobiles and ships, medical equipment, aerospace, etc. Optical materials with high transparency and high refractive index are key materials for advanced optical devices. The refractive index of traditional organic optical materials such as polystyrene, polycarbonate, polymethyl methacrylate, etc. is only 1.49-1.59, which cannot meet the optical performance requirements of advanced optical devices.

[0003] According to the Lorentz-Lorenz equation, the refractive index of organic optical materials can be effectively increased by introducing highly polarizable atoms or groups such as phosphorus atoms, sulfur atoms, and selenium atoms. The increase in the refractive index of the material is often accompanied by an increase in dispersion (i.e., a decrease in the Abbe number), which can lead to a decrease in imaging quality. Efficiently introducing sulfur atoms and their groups with high molar refractive index has become the most effective method for preparing optical materials with balanced refractive index and Abbe number. Summary of the invention

[0004] In order to solve the deficiencies of the prior art, the present invention provides a sulfur-containing oligomer and its application and an optical material composition.

[0005] The technical solution provided by the present invention is as follows:

[0006] A sulfur-containing oligomer, comprising one or more compounds having the structural formula shown in Formula 1: or, any one of the compounds having the structural formula shown in Formula 1 and a compound having an ethylenically unsaturated group is copolymerized; the ethylenically unsaturated group compound is selected from the structural formula shown in Formula 2: X is selected from O or S, R3 is H or methyl; R1 and R2 are selected from alkylene groups having 1 to 30 carbon atoms, alkyleneoxy groups having 1 to 15 carbon atoms, cycloalkyl groups having 3 to 20 carbon atoms, and aryl groups having 6 to 24 carbon atoms;

[0007] Any one or more hydrogen atoms in the alkylene group having 1 to 30 carbon atoms, the alkyleneoxy group having 1 to 15 carbon atoms, the cycloalkyl or heterocycloalkyl group having 3 to 20 carbon atoms, and the aryl group having 6 to 24 carbon atoms may be substituted by R', and the R' is selected from H, an alkyl group having 1 to 15 carbon atoms, an aryl group having 6 to 24 carbon atoms, and a cycloalkyl group having 3 to 10 carbon atoms; at least one of R1 or R2 is selected from an alkylene group having 1 to 30 carbon atoms.

[0008] The sulfur-containing oligomer is obtained by copolymerizing two compounds represented by Formula 1 or by reacting a compound represented by Formula 1 with a compound represented by Formula 2.

[0009] Preferably, the sulfur-containing oligomer is obtained by reacting the compound represented by Formula 1 with the compound represented by Formula 2, and in the obtained sulfur-containing oligomer, any R1 or R2 is selected from an alkylene group having 1 to 30 carbon atoms. That is, when R1 is selected from an alkylene group having 1 to 30 carbon atoms, R2 is selected from a cycloalkyl group having 3 to 20 carbon atoms and an aryl group having 6 to 24 carbon atoms; or, when R2 is selected from an alkylene group having 1 to 30 carbon atoms, R1 is selected from a cycloalkyl group having 3 to 20 carbon atoms and an aryl group having 6 to 24 carbon atoms.

[0010] Further preferably, the alkylene group having 1 to 30 carbon atoms is selected from straight-chain alkylene groups.

[0011] Preferably, when R1 is selected from an alkylene group having 1 to 30 carbon atoms, R2 is preferably an aryl group having 6 to 24 carbon atoms;

[0012] Or, more preferably, R2 is selected from an alkylene group having 1 to 30 carbon atoms, and R1 is preferably a cycloalkyl group having 3 to 20 carbon atoms.

[0013] Furthermore, the sulfur-containing oligomer has the structural formula shown in Formula 3: n is a natural integer of 1-500; the R2 is selected from an alkylene group having 1 to 15 carbon atoms, an alkyleneoxy group having 1 to 10 carbon atoms, a cycloalkyl group having 3 to 10 carbon atoms, and an aryl group having 6 to 24 carbon atoms; any one or more hydrogen atoms in the alkylene group having 1 to 15 carbon atoms, the alkyleneoxy group having 1 to 10 carbon atoms, the cycloalkyl group having 3 to 20 carbon atoms, and the aryl group having 6 to 24 carbon atoms may be replaced by the R'.

[0014] Preferably, n is a natural integer of 1-200; more preferably, it is a natural integer of 1-100; most preferably, n is a natural integer of 2-20.

[0015] Further preferably, the alkylene group having 1 to 15 carbon atoms is selected from straight-chain alkylene groups.

[0016] Furthermore, the cycloalkyl group having 3 to 10 carbon atoms is selected from saturated or unsaturated cycloalkyl groups having 5 to 8 carbon atoms.

[0017] Furthermore, the saturated or unsaturated cycloalkyl group having 5 to 8 carbon atoms is substituted with at least one S atom.

[0018] Furthermore, the cycloalkyl group having 3 to 10 carbon atoms has the structural formula shown in Formula 1-1 or 1-2 Each Z is independently selected from N, O, S or CR4, and the R4 is selected from H, an alkyl group having 1 to 15 carbon atoms, an alkoxy group having 1 to 15 carbon atoms, a cycloalkyl group having 3 to 20 carbon atoms or an aryl group having 6 to 24 carbon atoms; any one or more hydrogen atoms in the alkyl group having 1 to 15 carbon atoms, the alkoxy group having 1 to 15 carbon atoms, the cycloalkyl group having 3 to 20 carbon atoms or the aryl group having 6 to 24 carbon atoms may be replaced by the R'; the aryl group having 6 to 24 carbon atoms is bonded to or fused with an adjacent ring; and at least one of the X is selected from an S atom.

[0019] Furthermore, when the structural formula 1-1 is selected from unsaturated cycloalkyl groups, at least one of the Xs is selected from N or O atoms.

[0020] Furthermore, the formula 1-1 is specifically selected from the following structural formulas:

[0021] Furthermore, at least one X in the structural formula 1-1 is selected from N atoms. That is, in the technical solution of the present application, the structural formula 1-1 is preferably Further preferably, Formula 1-1 is preferably

[0022] Furthermore, at least one Z in the structural formula 1-2 is selected from a S atom.

[0023] Further preferably, the aromatic group having 6 to 24 carbon atoms has two or more phenyl groups, and the multiple phenyl groups are connected by any one or more of a single bond, fusion or -R5-; the R5 is selected from an alkyl group having 1-5 carbon atoms, O, S, C=O, SO2, NR6, and the R6 is selected from an alkyl group having 1-5 carbon atoms, and multiple adjacent phenyl groups can be fused.

[0024] Further preferably, the aryl group having 6 to 24 carbon atoms has the following structural formula: R7 is selected from alkyl with 1 to 5 carbon atoms, O, S, C=O, SO2, NR 10 , the R 10 is selected from alkyl groups having 1 to 5 carbon atoms, is empty or a single bond; R8 and R9 are selected from alkyl with 1 to 5 carbon atoms, O, S, C=O, SO2, NR 11 , the R 11 is selected from alkyl groups having 1 to 5 carbon atoms.

[0025] More preferably, R8 and R9 are the same and are selected from O or S.

[0026] For example, the aryl group having 6 to 24 carbon atoms may be selected from the following:

[0027]

[0028] In a second aspect, an optical material composition comprises the sulfur-containing oligomer.

[0029] A third aspect provides an application of a sulfur-containing oligomer, wherein the optical material composition is applied to display devices, optical lenses and optical devices.

[0030] According to the technical solution of the present invention, a dithiol compound or a monomer containing an unsaturated group at the end is reacted, and a click chemistry reaction between the thiol group and the double bond is used to obtain a high-refractive oligomer. After the reaction is completed, the S element will be retained on the main chain, and the S element content in the finally obtained oligomer is very high, so that the refractive index is greatly improved. In addition, the monomer containing an unsaturated group contains an alkyl chain, which increases the flexibility of the oligomer, so that the obtained optical resin has good fluidity and mechanical properties. DETAILED DESCRIPTION

[0031] The principles and features of the present invention are described below. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.

[0032] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0033] In the embodiments of the present invention, the degree of polymerization of the oligomer is n=10-20.

[0034] Embodiment 1:

[0035]

[0036] In a 50 ml flask, (1.08 g, 10 mmol) A1 (CAS: 109-80-8) and (1.82 g, 10 mmol) B1 (CAS: 14970-87-7) were dissolved in 20 ml tetrahydrofuran and stirred at room temperature for 4 h. The reaction status of the raw materials was confirmed by TLC spot plate, and the molecular weight of the polymer was detected by GPC. After the reaction was completed, the solvent tetrahydrofuran was spin-dried to obtain a polymer powder, which was washed with ethanol and deionized water in turn and vacuum dried to obtain C1 with a molecular weight Mw = 6564.

[0037] Embodiment 2:

[0038]

[0039] In a 50 ml flask, (1.08 g, 10 mmol) A2 (CAS: 109-80-8) and (2.34 g, 10 mmol) B2 (CAS: 17527-79-6) were dissolved in 20 ml tetrahydrofuran and stirred at room temperature for 4 h. The reaction status of the raw materials was confirmed by TLC spot plate, and the molecular weight of the polymer was detected by GPC. After the reaction was completed, the solvent tetrahydrofuran was spin-dried to obtain a polymer powder, which was washed with ethanol and deionized water in turn and vacuum dried to obtain C2 with a molecular weight Mw = 5748.

[0040] Embodiment 3:

[0041]

[0042] In a 50 ml flask, (1.08 g, 10 mmol) A3 (CAS: 109-80-8) and (2.12 g, 10 mmol) B3 (CAS: 136122-15-1) were dissolved in 20 ml tetrahydrofuran and stirred at room temperature for 4 h. The reaction status of the raw materials was confirmed by TLC spot plate, and the molecular weight of the polymer was detected by GPC. After the reaction was completed, the solvent tetrahydrofuran was spin-dried to obtain a polymer powder, which was washed with ethanol and deionized water in turn and vacuum dried to obtain C3 with a molecular weight Mw = 5690.

[0043] Embodiment 4:

[0044]

[0045] In a 50 ml flask, (1.08 g, 10 mmol) A4 (CAS: 109-80-8) and (1.48 g, 10 mmol) B4 (CAS: 22511-31-5) were dissolved in 20 ml tetrahydrofuran and stirred at room temperature for 4 h. The reaction status of the raw materials was confirmed by TLC spot plate, and the molecular weight of the polymer was detected by GPC. After the reaction was completed, the solvent tetrahydrofuran was dried to obtain a polymer powder, which was washed with ethanol and deionized water in turn and vacuum dried to obtain C4 with a molecular weight of Mw = 4286.

[0046] Embodiment 5:

[0047]

[0048] In a 50 ml flask, (1.08 g, 10 mmol) A5 (CAS: 109-80-8) and (1.50 g, 10 mmol) B5 (CAS: 132120-63-9) were dissolved in 20 ml tetrahydrofuran and stirred at room temperature for 4 h. The reaction status of the raw materials was confirmed by TLC spot plate, and the molecular weight of the polymer was detected by GPC. After the reaction was completed, the solvent tetrahydrofuran was spin-dried to obtain a polymer powder, which was washed with ethanol and deionized water in turn and vacuum dried to obtain C5 with a molecular weight Mw = 4066.

[0049] Embodiment 6:

[0050]

[0051] In a 50 ml flask, (1.08 g, 10 mmol) A6 (CAS: 109-80-8) and (3.64 g, 10 mmol) B6 (CAS: 3253-39-2) were dissolved in 20 ml tetrahydrofuran and stirred at room temperature for 4 h. The reaction status of the raw materials was confirmed by TLC spot plate, and the molecular weight of the polymer was detected by GPC. After the reaction was completed, the solvent tetrahydrofuran was dried to obtain a polymer powder, which was washed with ethanol and deionized water in turn and vacuum dried to obtain C6 with a molecular weight of Mw = 7082.

[0052] Embodiment 7:

[0053]

[0054] In a 50 ml flask, (1.08 g, 10 mmol) A7 (CAS: 109-80-8) and (3.70 g, 10 mmol) B7 (CAS: 1359657-36-5) were dissolved in 20 ml tetrahydrofuran and stirred at room temperature for 4 h. The reaction status of the raw materials was confirmed by TLC spot plate, and the molecular weight of the polymer was detected by GPC. After the reaction was completed, the solvent tetrahydrofuran was dried to obtain a polymer powder, which was washed with ethanol and deionized water in turn and vacuum dried to obtain C7 with a molecular weight Mw = 6962.

[0055] Embodiment 8:

[0056]

[0057] In a 50 ml flask, (1.08 g, 10 mmol) A8 (CAS: 109-80-8) and (3.66 g, 10 mmol) B8 (CAS: 2425533-69-1) were dissolved in 20 ml tetrahydrofuran and stirred at room temperature for 4 h. The reaction status of the raw materials was confirmed by TLC spot plate, and the molecular weight of the polymer was detected by GPC. After the reaction was completed, the solvent tetrahydrofuran was dried to obtain a polymer powder, which was washed with ethanol and deionized water in turn and vacuum dried to obtain C8 with a molecular weight Mw = 6164.

[0058] Embodiment 9:

[0059]

[0060] In a 50 ml flask, (1.84 g, 10 mmol) A9 (CAS: 645404-26-8) and (2.54 g, 10 mmol) B9 (CAS: 6606-59-3) were dissolved in 20 ml tetrahydrofuran and stirred at room temperature for 4 h. The reaction status of the raw materials was confirmed by TLC spot plate, and the molecular weight of the polymer was detected by GPC. After the reaction was completed, the solvent tetrahydrofuran was spin-dried to obtain a polymer powder, which was washed with ethanol and deionized water in turn and vacuum dried to obtain C9 with a molecular weight Mw = 5696.

[0061] Embodiment 10:

[0062]

[0063] In a 50 ml flask, (1.5 g, 10 mmol) A10 (CAS: 132120-63-9) and (2.54 g, 10 mmol) B10 (CAS: 6606-59-3) were dissolved in 20 ml tetrahydrofuran and stirred at room temperature for 4 h. The reaction status of the raw materials was confirmed by TLC spot plate, and the molecular weight of the polymer was detected by GPC. After the reaction was completed, the solvent tetrahydrofuran was dried to obtain a polymer powder, which was washed with ethanol and deionized water in turn and vacuum dried to obtain C10 with a molecular weight Mw = 5254.

[0064] Comparative Example 1:

[0065]

[0066] In a 50 ml flask, (1.52 g, 10 mmol) A8 (CAS: 856940-26-6) and (3.64 g, 10 mmol) B8 (CAS: 3253-39-2) were dissolved in 20 ml tetrahydrofuran and stirred at room temperature for 4 h. The reaction status of the raw materials was confirmed by TLC spot plate, and the molecular weight of the polymer was detected by GPC. After the reaction was completed, the solvent tetrahydrofuran was spin-dried to obtain a polymer powder, which was washed with ethanol and deionized water in turn and vacuum dried to obtain S8 with a molecular weight Mw = 7226.

[0067] Performance testing:

[0068] Film refractive index test: The sample molecules were dissolved in THF and spin-coated on a silicon wafer to prepare an optical film (Step-1: 500rpm, 10s; Step-2: 2000rpm, 50s); the viscosity at 25°C was tested using a viscometer; the film was then pre-baked at 90°C for 3min, and then optical fitting was performed using an ellipsometer, and the refractive index and extinction coefficient of the film were tested using an Abbe refractometer; the Abbe number was measured using an Abbe refractometer; the test results are shown in Table 1 below. The test results are shown in Table 1 below:

[0069] Table 1

[0070]

[0071] It can be seen from the above table that the sulfur-containing oligomer obtained in the embodiment of the technical solution of the present invention has a refractive index adjustable within the range of 1.65-1.75, a high transmittance, and excellent optical properties such as Abbe number and extinction coefficient.

[0072] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A sulfur-containing oligomer, characterized in that: Obtained by copolymerizing any one or more compounds having the structural formula shown in Formula 1, or obtained by copolymerizing any one compound having the structural formula shown in Formula 1 with a compound having an ethylenically unsaturated group; The structural formula shown in formula 1 is as follows: The compound having an ethylenically unsaturated group is selected from the structural formula shown in Formula 2: in: X is selected from O or S, and R3 is H or methyl; R1 and R2 are independently selected from substituted or unsubstituted alkylene groups having 1 to 30 carbon atoms, substituted or unsubstituted alkyleneoxy groups having 1 to 15 carbon atoms, substituted or unsubstituted cycloalkyl or heterocycloalkyl groups having 3 to 20 carbon atoms, and substituted or unsubstituted aryl groups having 6 to 24 carbon atoms, and at least one of R1 or R2 is selected from the alkylene groups having 1 to 30 carbon atoms; the substituents are selected from alkyl groups having 1 to 15 carbon atoms, aryl groups having 6 to 24 carbon atoms, and cycloalkyl groups having 3 to 10 carbon atoms, and the number of substituents is at least one.

2. The sulfur-containing oligomer according to claim 1, characterized in that It has the structural formula shown in Formula 3: n is a natural integer from 1 to 500; The R2 is selected from a substituted or unsubstituted alkylene group having 1 to 15 carbon atoms, a substituted or unsubstituted alkyleneoxy group having 1 to 10 carbon atoms, a substituted or unsubstituted cycloalkyl group having 3 to 10 carbon atoms, and a substituted or unsubstituted aryl group having 6 to 24 carbon atoms; The substituent is selected from an alkyl group having 1 to 15 carbon atoms, an aryl group having 6 to 24 carbon atoms, and a cycloalkyl group having 3 to 10 carbon atoms, and the number of the substituent is at least one.

3. The sulfur-containing oligomer according to claim 2, characterized in that: The cycloalkyl group having 3 to 10 carbon atoms is selected from saturated or unsaturated cycloalkyl groups having 5 to 8 carbon atoms.

4. The sulfur-containing oligomer according to claim 3, characterized in that: The saturated or unsaturated cycloalkyl group having 5 to 8 carbon atoms has at least one S.

5. The sulfur-containing oligomer according to claim 3, characterized in that: The cycloalkyl group having 3 to 10 carbon atoms has the structural formula shown in Formula 1-1 or 1-2: in: each Z is independently selected from N, O, S or CR4, said R4 is selected from H, substituted or unsubstituted alkyl having 1 to 15 carbon atoms, substituted or unsubstituted alkoxy having 1 to 15 carbon atoms, substituted or unsubstituted cycloalkyl having 3 to 20 carbon atoms or aryl having 6 to 24 carbon atoms; The aromatic group having 6 to 24 carbon atoms is bonded or fused to an adjacent ring; At least one of said Z is selected from S atoms; The substituent is selected from an alkyl group having 1 to 15 carbon atoms, an aryl group having 6 to 24 carbon atoms, and a cycloalkyl group having 3 to 10 carbon atoms, and the number of the substituent is at least one.

6. The sulfur-containing oligomer according to claim 5, characterized in that: When the structural formula 1-1 is selected from an unsaturated cycloalkyl group having 5 to 8 carbon atoms, at least one of the Z atoms is selected from N or O atoms.

7. The sulfur-containing oligomer according to claim 5, characterized in that: When the structural formula 1-1 is selected from an unsaturated cycloalkyl group of 5 to 8 carbon atoms, it has the following structural formula:

8. The sulfur-containing oligomer according to claim 2, characterized in that: The aromatic group having 6 to 24 carbon atoms has two or more phenyl groups, and the multiple phenyl groups are connected to R5 by any one or more means of single bond, fusion or -R5-; The R5 is selected from an alkyl group having 1 to 5 carbon atoms, O, S, C=O, SO2, NR6, and the R6 is selected from an alkyl group having 1 to 10 carbon atoms.

9. An optical material composition, characterized in that: At least comprising the sulfur-containing oligomer according to any one of claims 1 to 8.

10. Use of the sulfur-containing oligomer according to any one of claims 1 to 8, characterized in that: For preparing display devices or optical devices; Alternatively, it can be used to prepare optical lenses.